Effect of applying oyster shell powder on soil properties and microbial diversity in the acidified soils of pomelo garden - Yuanyuan Li; Qiong Zhang; Lixia Zhu; Jing Yang; Jingjing Wei; Yunhe Li; Xiaohuang Chen (Environmental Microbiome)
Abstract The application of oyster shell has recently been used to increase soil pH in Southern China. However, little is known about causal shifts in the rhizosphere microbial community of pomelo trees, especially in orchards that have experienced natural accumulation of heavy metals over many years due to continuous fertilization and soil acidification. This study evaluated the effects of oyster shell powder applied for 1 year (T1), 2 years (T2) and 3 years (T3), alongside a control group with no soil amendments (Control; CK), on soil acidification and microbial diversity. Our findings demonstrated that the application of oyster shell significantly increased soil pH and reduced the concentrations of heavy metals such as thallium (Tl), chromium (Cr), and manganese (Mn). Illumina sequencing-based community analysis revealed that oyster shell application significantly increased the alpha diversity indices of both bacterial and fungal communities and influenced their distribution in the soil. Notably, all oyster shell-treated groups (T1-T3) showed significantly higher relative abundances of beneficial microbes (e.g., Nitrolancea, Vicinamibacterales) and those involved in carbohydrate degradation and nitrogen fixation compared to the control. Conversely, the relative abundances of Acidibacter and Chujaibacter (associated with heavy metal degradation and soil-borne diseases), Trichoderma and Acremonium (plant-beneficial fungi), as well as functionally annotated groups linked to nitrogen assimilation and pathotrophic modes (predicted via FUNGuild analysis), decreased significantly. Our results suggest that the application of oyster shell powder amendments contributes to improved soil properties and microbial environments; however, the effects on soil nitrogen cycling and fungal function are complex, warranting further research.